The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1086/499970
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐Dihydroxyvitamin D3 Enhances Systemic and Mucosal Immune Responses to Inactivated Poliovirus Vaccine in Mice

Abstract: 1,25-Dihydroxyvitamin D3 (DHVD3) coadministered with monovalent inactivated poliovirus vaccine (IPV) of all 3 serotypes significantly enhances antipoliovirus systemic and mucosal immunity in mice. Although serum immunoglobulin G antibodies are significantly higher in serotypes 2 and 3, and although salivary immunoglobulin A is significantly increased in serotypes 1 and 3, DHVD3 had the most dramatic effect on the level of neutralizing serum antibodies of all 3 IPV serotypes. These findings suggest a possible u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 9 publications
1
42
0
2
Order By: Relevance
“…In contrast, the data indicate that induction of TT-specific IgG was marginally more efficient in vitamin D compared with the placebo group (P ¼ 0.04). These data are in line with previous studies (Ivanov et al, 2006;Enioutina et al, 1999Enioutina et al, , 2008Van der Stede et al, 2001) and attributed most likely to induction of specific IgG1, which is the dominant subclass induced by the vaccination used herein (492% of the circulating specific plasmablasts; Frolich et al, 2010). That vitamin D supplementation did not alter the specific Peripheral blood mononuclear cells were activated before and 7 days after a Tet immunization for 24 h in the presence of Tet or SEB, and the secreted cytokines were determined from the supernatants.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, the data indicate that induction of TT-specific IgG was marginally more efficient in vitamin D compared with the placebo group (P ¼ 0.04). These data are in line with previous studies (Ivanov et al, 2006;Enioutina et al, 1999Enioutina et al, , 2008Van der Stede et al, 2001) and attributed most likely to induction of specific IgG1, which is the dominant subclass induced by the vaccination used herein (492% of the circulating specific plasmablasts; Frolich et al, 2010). That vitamin D supplementation did not alter the specific Peripheral blood mononuclear cells were activated before and 7 days after a Tet immunization for 24 h in the presence of Tet or SEB, and the secreted cytokines were determined from the supernatants.…”
Section: Discussionsupporting
confidence: 90%
“…While the role of vaccinations in the etiology of autism is not clear, higher levels of calcidiol could reduce the risk of adverse reactions to vaccinations, based on reports that calcidiol reduces the risk of respiratory viral infections and that calcitriol enhances the effectiveness of vaccinations. [55][56][57][58] …”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously reported that both systemic and mucosal antigen-specific immune responses can be induced in mice and other animal species following parenteral immunization with protein vaccines containing small quantities of 1α25(OH) 2 D 3 [17][18][19]21,22,37,38]. The mucosal antibody responses induced by these systemically administered vaccines were established to reflect local production by IgA-secreting B cells residing in the lamina propria, and the levels of antigen-specific IgA antibodies present in the mucosal secretions were determined to be independent of serum antibody titers [18].…”
Section: Discussionmentioning
confidence: 99%